Molecular Diversity and Association Analysis of Drought and Salt Tolerance in Gossypium hirsutum L. Germplasm - Yin-hua JIA; Jun-ling SUN; Xi-wen WANG; Zhong-li ZHOU; Zao-e PAN; Shou-pu HE; Bao-yin PANG; Li-ru WANG; Xiong-ming DU (Journal of Integrative Agriculture, 2014)
Association mapping is a useful tool for the detection of genes selected during plant domestication based on their linkage disequilibrium (LD). This study was carried out to estimate genetic diversity, population structure and the extent of LD to develop an association framework in order to identify genetic variations associated with drought and salt tolerance traits. 106 microsatellite marker primer pairs were used in 323 Gossypium hirsutum germplasms which were grown in the drought shed and salt pond for evaluation. Polymorphism (PIC=0.53) was found, and three groups were detected (K=3) with the second likelihood ΔK using STRUCTURE software. LD decay rates were estimated to be 13-15 cM at r2≥0.20. Significant associations between polymorphic markers and drought and salt tolerance traits were observed using the general linear model (GLM) and mixed linear model (MLM) (P≤0.01). The results also demonstrated that association mapping within the population structure as well as stratification existing in cotton germplasm resources could complement and enhance quantitative trait loci (QTLs) information for marker-assisted selection.